A thermochemical study on the primary oxidation of sulfur. Issue 1 (2nd January 2019) - Sebbar, N.; Bozzelli, J.W.; Bockhorn, H.; Trimis, D.
ABSTRACT: Several chemical reactions related to the oxidation and combustion of sulfur are investigated using a number of computational chemistry methods with the objective of determining appropriate methods for use in developing an elementary reaction mechanism for oxidation of sulfur. Calculations are focused on thermochemical properties and reaction energetics for reactive species and transition state structures for reactions in the oxidation/combustion of sulfur. Reactions involving several intermediates resulting from the reactions of S2 with oxygen were investigated with the density functional theory B3LYP (with several basis sets) and BB1K/GTLarge. The composite ab-initio methods G2, G3, G3MP2, G3B3, G3MP2B3 and CBS-QB3 were also used. Enthalpies of a series of sulfur compounds and transition state structures are calculated using the ab-initio and DFT calculations. The calculations were combined with isodesmic reaction analysis, whenever possible, in order to cancel error and improve the accuracy of the calculations. Results show that all B3LYP DFT calculations including the 6–311++G(3df, 2p) basis set show poor outcome in estimating the enthalpy of reactions involving S2 . The six composite methods have all shown consistency with each other and their calculated reaction energies/bond energies are in good agreement with the available literature. Kinetic parameters for calculation of the kinetic parameters on SO3 dissociation to SO2 and O using the canonical transition state theory are reported.